Unbalanced development of inter-provincial high-grade highway in China: Decomposing the Gini coefficient. (October 2016) - Chen, Jiandong; Chen, Jiantao; Miao, Yi; Song, Malin; Fan, Yingjie
Highlights: We discuss unbalanced development of Chinese inter-provincial high-grade highway. The main approaches are different methods of decomposing the Gini coefficient. There is a declining trend of unbalanced distribution of highway from 1997 to 2013. The government should focus more on protecting environment during construction. Abstract: This study discusses the unbalanced development of Chinese inter-provincial high-grade highway from 1997 to 2013. It does so from the viewpoint of the inter-provincial Gini coefficient based on per capita mileage of high-grade highway, which is decomposed according to such dimensions as the increment of the Gini coefficient, the Gini coefficient of different types of high-grade highway, and the Gini coefficient between and within inland and coastal areas. The Gini coefficient of China's per capita mileage of inter-provincial high-grade highway shows a declining trend year by year. According to the results from the decomposition of the contribution rate of different types of high-grade highway, the unbalanced development of inter-provincial high-grade highway is caused mainly by that of first- and second-grade highway. According to the results from the decomposition related to the increment of the Gini coefficient of China's per capita mileage of inter-provincial high-grade highway, the decrease of the Gini coefficient from 1997 to 2013 was mainly the result of balanced distribution of high-grade highway among regions in China. According to the results from the decomposition of the Gini coefficient between and within inland and coastal areas, the unbalanced development of inter-provincial high-grade highway in China from 1997 to 2013 was caused mainly by the unbalanced development of inter-provincial high-grade highway in inland areas. Therefore, the authors argue that the government should pay more attention to protecting the environment and providing a suitable scale of highway network, which could promote long-term sustainable development.